2020
DOI: 10.18845/tm.v33i1.5027
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de concentraciones de cadmio en plantaciones de Theobroma cacao L. en Costa Rica

Abstract: El cultivo de cacao se mantiene en auge en Costa Rica; sin embargo, las autoridades europeas han establecido regulaciones a la importación de los derivados del cacao; las cuales iniciaron en enero de 2019 con la fijación de niveles de concentración máximos permitidos de cadmio. El objetivo de este trabajo fue determinar concentraciones de cadmio en suelo, raíz, hoja y en grano seco no fermentado de cacao en dos regiones productoras de este cultivo en el país.  El presente estudio exploratorio se realizó en 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…It was observed that the presence of Cd in the crop caused the appearance of chlorosis in both treatments (2% and 10%-OM) due to a decrease in chlorophyll, which was more evident as the metal concentration increased in the crop treatments. Chlorosis represents a sign of metallic toxicity due to interference in the absorption of essential elements in the photosynthetic process; since Cd can compete in the absorption and transport through essential elements such as Ca, Mg or Fe, causing stomata closure and resulting in an inhibition of photosynthesis, thus plant growth is considerably affected by nutrient imbalance (Nazar et al, 2012;Furcal-Beriguete & Torres-Morales, 2020;Rodríguez, 2007). It has also been reported that Cd is related to the reduction and transport of Mn, which acts as an energy catalyst in the photosynthetic process and interferes with the entry and transport of Ca, P and K, causing a delay in plant growth and inhibition of photosynthetic processes (Seregin & Kozhevnikova, 2008;Benavides, 2011;Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the presence of Cd in the crop caused the appearance of chlorosis in both treatments (2% and 10%-OM) due to a decrease in chlorophyll, which was more evident as the metal concentration increased in the crop treatments. Chlorosis represents a sign of metallic toxicity due to interference in the absorption of essential elements in the photosynthetic process; since Cd can compete in the absorption and transport through essential elements such as Ca, Mg or Fe, causing stomata closure and resulting in an inhibition of photosynthesis, thus plant growth is considerably affected by nutrient imbalance (Nazar et al, 2012;Furcal-Beriguete & Torres-Morales, 2020;Rodríguez, 2007). It has also been reported that Cd is related to the reduction and transport of Mn, which acts as an energy catalyst in the photosynthetic process and interferes with the entry and transport of Ca, P and K, causing a delay in plant growth and inhibition of photosynthetic processes (Seregin & Kozhevnikova, 2008;Benavides, 2011;Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most studies on Cd absorption and accumulation in young cacao plants are carried out using soils or substrates artificially enriched with soluble sources of Cd, such as cadmium chloride (CdCl 2 ) [8,11] and cadmium nitrate (Cd (NO 3 ) 2 ) [12]. Likewise, studies conducted in Cd-contaminated soils without the addition of specific sources of this heavy metal have been conducted in plantations with an age exceeding ten years [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…En el mismo sentido, Argüello et al, (2019) analizaron 254 muestras de cacao ecuatoriano y hallaron niveles de Cd de 0,030 a 10,400 mg/kg con una media geométrica de 0,550 mg/kg y una media aritmética de 0,900 mg/kg de Cd, donde el 45% de las muestras superaron el límite permisible. Se ha sugerido que la contaminación del cacao se debe al Cd presente en el suelo de manera natural por la actividad volcánica, al uso de fertilizantes y al agua para riego contaminada con este metal pesado (Mite et al, 2010;Chávez et al, 2015;Chávez et al, 2016;Barraza et al, 2018;Kruszewski et al, 2018;Furcal-Beriguete & Torres-Morales, 2020;Argüello et al, 2021). Dentro de los metales pesados se han descrito el arsénico, el cadmio y el plomo como los más tóxicos presentes en el cacao (Abt et al, 2018;Anyimah-Ackah et al, 2018), y de los derivados del cacao el chocolate en polvo es uno de los productos más consumidos y en especial por los niños, donde la presencia de metales pesados representa un riesgo para su salud y una preocupación pública (Abt et al, 2018;Anyimah-Ackah et al, 2018;Maddela et al, 2020).…”
Section: Introductionunclassified